Unmasking Extramammary Paget Disease: A Case Report on the Importance of Biopsy in Persistent Dermatitis - Riswanto, Cintya Dipta; Widia, Yuri; Kusumaputra, Bagus Haryo; Sari, Maylita; Citrashanty, Irmadita; Listiawan, M. Yulianto (Journal of Neonatal Surgery, 2025)
Introduction: Extramammary Paget’s disease (EMPD) is a very rare cutaneous neoplasm that occurs predominantly in locations with apocrine glands. In Asia, the incidence of EMPD is extremely low, ranging from 0.04 to 0.12 cases per 100,000 population. The clinical features of EMPD resemble chronic inflammation, making it difficult to distinguish from other skin disorders. Here, we present a rare case of EMPD in Indonesia. Case report: A 67-year-old woman presented with a 5-year history of erythematous plaque over her vulva and pubic area. The cutaneous lesions were painful and progressed slowly. Lesions manifest as well-defined erythematous plaques with irregular margins, an overlying scale or crust, and hypopigmentation or hyperpigmentation. The patient had received topical treatment for one year, but the condition remained unchanged. Histopathologic findings showed infiltration of anaplastic cells with round, pleomorphic, and hyperchromatic nuclei. Immunohistochemical staining showed CK7+, CK20-, p63+, and GATA3+. The growth confines itself to the epidermis, without penetrating the basal membrane. Discussion: A comprehensive examination, including lymph node palpation, can diagnose EMPD, and a skin biopsy and histopathology confirm the diagnosis. Immunohistochemical staining is essential for ruling out other possible diagnoses. Surgery is the primary treatment for EMPD. Given the risk of recurrence and additional malignancies, a close follow-up is recommended for the first 5 years. Conclusion: The diagnosis of EMPD is a challenge due to the nonspecific clinical appearance, leading to delayed therapy. A skin biopsy is recommended for chronic anogenital skin lesions that don’t respond to topical therapy.